The Privilege of Servitude : The New Service Proletariat in the Digital Age - Antunes, Ricardo (Historical Materialism Book Series, 2026)
The Privilege of Servitude presents a detailed and up-to-date portrait of today's working class. Antunes examines the main trends in new labour relations, where precariousness, outsourcing, and deregulation have become the rule rather than the exception. He offers an in-depth analysis of the rise of the new service proletariat and contemporary forms of digital labour, while also exploring changes in labour relations globally-with a particular focus on Brazil's recent history, from the period of redemocratisation to the Bolsonaro years.